2016
DOI: 10.1002/bip.22821
|View full text |Cite
|
Sign up to set email alerts
|

Aryl–aryl interactions in designed peptide folds: Spectroscopic characteristics and optimal placement for structure stabilization

Abstract: We have extended our studies of Trp/Trp to other Aryl/Aryl through-space interactions that stabilize hairpins and other small polypeptide folds. Herein we detail the NMR and CD spectroscopic features of these types of interactions. NMR data remains the best diagnostic for characterizing the common T-shape orientation. Designated as an edge-to-face (EtF or FtE) interaction, large ring current shifts are produced at the edge aryl ring hydrogens and, in most cases, large exciton couplets appear in the far UV circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 54 publications
0
43
0
1
Order By: Relevance
“…[7] We chose these peptide systems because they all contain at least two Trp residues that have been shown to engage in exciton coupling and hence exhibit an exciton CD band. Finally, we investigated the Trp to Trp CN and Phe to Phe CN double mutant of another stable β-hairpin that was designed through “loop optimization” by Andersen and coworkers [20]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] We chose these peptide systems because they all contain at least two Trp residues that have been shown to engage in exciton coupling and hence exhibit an exciton CD band. Finally, we investigated the Trp to Trp CN and Phe to Phe CN double mutant of another stable β-hairpin that was designed through “loop optimization” by Andersen and coworkers [20]. …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study on the role of aryl-aryl interactions in β-hairpin folding, Andersen and coworkers [20] systematically examined the effect of various cross-strand interactions that can promote β-hairpin formation. In particular, they found that a peptide with the following sequence, KKYTFNPATGKWTVQE, can fold into a β-hairpin conformation at room temperature, due to a favorable Phe-Trp interaction with Trp occupying the face position and Phe at the edge position.…”
Section: Resultsmentioning
confidence: 99%
“…Cross‐strand Trp/Trp EtF interactions provide at least a 2.3–5 kJ/mol stabilization of hairpin folds . More recently, we have reported that end‐capping Trp/Trp EtF interactions produce a stabilization of 5–7 kJ/mol . Some stabilization also results from the interaction of the Gly‐H N with the indole ring of the C‐terminus Trp and the Thr hydroxyl group interacting with the C═O of the Trp‐alkanoyl peptide bond.…”
Section: Resultsmentioning
confidence: 92%
“…[13,18] More recently, we have reported that end-capping Trp/Trp EtF interactions produce a stabilization of 5-7 kJ/mol. [19] Some stabilization also results from the interaction of the Gly-H N with the indole ring of the C-terminus Trp and the Thr hydroxyl group interacting with the C═O of the Trpalkanoyl peptide bond. The stability of this cap has been shown to be higher, by~2 kJ/mol, than that conferred by some covalent stabilization strategies such as disulfide bonding.…”
Section: Resultsmentioning
confidence: 99%
“…The WWst29 system was designed in‐house, starting as a truncated version of the wild type protein Pin1 with the inclusion of a Trp/Trp aromatic cluster flanking T1 . The cross‐strand Trp/Trp cluster also reports the stability of the overall structure as the amplitude of a circular dichroic exciton couplet with maximum at 228 nm . In addition to this spectroscopic feature, the WW domain has numerous specific and well‐dispersed structuring chemical shifts that can be quantitated by proton NMR.…”
Section: Figurementioning
confidence: 99%